Efektivitas Strategi Rekrutmen Berbasis Job Training untuk Memperoleh Karyawan yang Memiliki Sikap Religiusitas serta Berkualitas : Studi pada KSPPS Tunas Artha Mandiri Syariah KC Magetan - Handayani, Rizky Estu; Damanuri, Aji (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The employee recruitment process is key in a company. Qualified employees are quality employees who show good human resources. KSPPS Tunas Artha Mandiri Syariah KC Magetan, in its employee recruitment, uses a job training strategy that is proven to be effective in providing employee outputs who have an attitude of religiosity and quality. This research uses a qualitative approach with descriptive analysis and field research. This research serves as a tool to understand the effectiveness of job training in the recruitment process and as a basis for decision-making. Recruitment process, but also as a basis for strategic decision-making related to human resource management at KSPPS Tunas Artha Mandiri. Decisions on human resource management at KSPPS Tunas Artha Mandiri Syariah KC Magetan. In addition, this analysis also allows the company to identify weaknesses and challenges that may arise in the implementation of job training.By knowing these obstacles, KSPPS can develop more effective and efficient improvement strategies. They are more appropriate and efficient in recruiting employees with superior competence. who have superior competence.